The Development of Ascaridia galli Infective Eggs by In Vitro Culture - Ummu Balqis; Darmawi D; Muhammad Hambal; Risa Tiuria (Jurnal Kedokteran Hewan, 2009)
The aim of this study was to determine the survival of embrionated eggs of Ascaridia galli. Adult female worms were obtained from lumen of intestine of native chickens in a slaughter house. Eggs obtained from the uteri of adult female worms were incubated in distilled water at room temperature for 20-31 days in order to develop A. galli infective eggs. The eggs were counted using stereomicroscope. The result showed that the amount of A. galli eggs were 1,045,478 and the amount of embrionated eggs were 935,300 (89.46%).Keywords: Ascaridia galli,  embrionated eggs